Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan terhadap Pengungkapan CSR dengan Pendekatan ISR di Bank BJB Syariah - Eka Yugi Meyliani; Nur’aeni Nur’aeni; Putri Zafira; Vemy Suci Asih (Jurnal Dimamu, 2023)
This research is motivated by the gap between theory and practice on ROA, FDR and Size so that it affects ISR. This study aims to determine how the influence of the disclosure of Corporate Social Responsibility with the Islamic Social Reporting approach partially and simultaneously at Bank BJB Syariah. The object of research in this report is the annual report and sustainability report of Bank BJB Syariah for the period 2017-2021. This type of research is quantitative associative with secondary data type and data collection in the form of documentation and literature study. While the sampling technique is financial ratios. Population is the annual report and sustainability report. The results showed that there was no significant effect between ROA and ISR with the results of t-test where the value of tcount < ttable (1,265 < 2,919), there was no significant effect between FRD and ISR with the results of tcount < ttable (-1,130 < 2,919), and there is a significant effect between Size and ISR with tcount > ttable (4.103 > 2.919), and simultaneously there is no significant effect between ROA, FDR and Size on ISR at BJB Syariah Bank with the results of the F test where the value of Fcount < Ftable (0 ,0012<216).